Gender in modern India: history, culture, marginality - Singh, Lata; Shekhar Sinha, Shashank (New York, USA: Oxford University Press, 2023)
"Gender is as much a political subject as an intellectual one. It has been the terrain over which "communities assert their superiority and the inferiority of others"; "nations claim their own purity and the contamination of others"; and "the West marks its development over the backwardness of others." Broadly speaking, there are three overlapping phases which gender studies has traversed in the past. The first one was 1970s. Women's movement and scholarship on gender, both began their modern journeys in the 1970s. 1970s was the decade of three significant developments which had a bearing on the future of gender. First, the disenchantment against post-independent model of planned development was manifesting in mass agitations and public protests in which women participated in an active way and in good numbers. Second, the publication of the report Towards Equality (1974)-emanating from a survey done by the 'Committee on the Status of Women in India' (CSWI) set up by the central government in 1971 to review rights and status, especially with respect to education and employment-showed the deplorable condition of women in the country, and how it was fast deteriorating. This galvanized many feminists and activists into action and was hailed as the foundational text of the movement. It also brought about a shift-from women as subjects to be educated to women as new subjects of investigation and study. Third, the Indian Council of Social Science Research (ICSSR), country's apex research body, started a program on women's studies (1975) to generate and analyze data and study women's question in relation to social sciences"--
Keywords: Feminism